How can Dance and Drama in the English Class Promote Fourth Graders’ Oral Production? (2021)
ABSTRACT : This paper reports a teaching and action research experience focused on improving students’ oralproduction by involving experience and reason in the English lessons. The experiences weremainly provided through dance and drama exercises. The project was implemented with fourthgraders of a Colombian public school. As results suggest, students easily acquired targetlanguage vocabulary and simple structures through the experiences offered by dance and drama;students improved in grammar components by repeating, singing and combining words withmovements, and gestures; students conveyed their messages better when they managed bodylanguage and the speed of speech; and students felt confident to speak since dance and dramapromoted a comfortable class environment.